TINJAUAN YURIDIS ASAS PEMBANGUNAN TENAGA KERJA DALAM PEMBERIAN PESANGON DI INDONESIA - Emilia Metta Wijaya (Justitia et Pax, 2022)
Economic growth can realize by increasing investment. Unfortunately, investors are not interested in investing in Indonesia because of the large amount of severance pay for workers. Regulatory adjustments are needed to meet the demands of investors while still paying attention to the principles of labor development. Therefore, this research focuses on the issues of determining and analyzing juridically the principles of labor development in giving severance pay in Indonesia. This research is a normative legal research that focuses on positive legal norms in the form of legislation. The result of this research shows that the provision of severance pay for workers in Indonesia is not currently under the principles of labor development. This is because the regulated severance pay that should be provided in order to develop workers actually taking away workers prosperity.